Review of Reconfigurable Antennas for LTE, WiMAX and WLAN Application - A. A. Palsokar; S. L. Lahudkar (Advanced Electromagnetics, 2017)
To satisfy the requirement of advance wireless system various frequency and pattern reconfigurable antennas are designed. Monopole and PIFA antennas with reconfigurability are preferred for various handheld devices. The objective of this paper was to present a review of reconfigurable monopole and PIFA antennas used for LTE, WiMAX and WLAN frequency ranges. Various optimization techniques used for reconfigurable antenna are also reviewed.